2011
DOI: 10.1111/j.1742-1241.2011.02773.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment of South Asians in a religious setting: a feasibility study

Abstract: Summary Aims:  South Asians in the UK have high cardiovascular disease (CVD) mortality. Therefore, this population is likely to benefit from screening programmes. To address this issue, an initiative was set up between the Royal Free Hampstead NHS Trust, H.E.A.R.T. UK and two Hindu temples in North London to provide screening for CVD risk factors in the community. Methods:  A total of 434 individuals of Gujarati Indian origin were screened. Measurements included anthropometry, blood pressure and lipid profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Davachi et al [46] demonstrated that when diabetes screening sessions for those without known diabetes were held in the context of religious gatherings in temples and mosques in Calgary, Alberta, it was highly acceptable to community members and is reflected in the high participation rate (922 screened in 14 four hour screening sessions). Similarly, Rao et al [45] screened for CVD risk in two Hindu temples in London, England. In this study medical/paramedical community members were able to screen 434 self-selected participants in 9 six-hour sessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Davachi et al [46] demonstrated that when diabetes screening sessions for those without known diabetes were held in the context of religious gatherings in temples and mosques in Calgary, Alberta, it was highly acceptable to community members and is reflected in the high participation rate (922 screened in 14 four hour screening sessions). Similarly, Rao et al [45] screened for CVD risk in two Hindu temples in London, England. In this study medical/paramedical community members were able to screen 434 self-selected participants in 9 six-hour sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Using a methodology similar to ours, Davachi et al [46] opportunistically screened adult non-diabetic SA for diabetes in places of worship, and observed very high rates of obesity (67%), family history of diabetes (43%) and results suggestive of potential glucose intolerance (36%). Despite excluding of those with self reported CVD, hypertension, diabetes or use of lipid therapy, [45] Rao et al found that 52% of participants had hypertension, 75% had central obesity, 10% had TC/HDL ratios > 6, and 15% were assessed as high risk using the QRISK2 model for 10-year CVD risk. The higher prevalence of both poorly controlled risk factors and 10-year CVD risk among participants in our study are consistent with their higher average age and their relatively high prevalence of self-reported CVD (10%), diabetes (23%), hypertension (52%) and dyslipidemia (49%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐traditional screening strategies such as the use of religious meeting places (e.g. Hindu temples) seems to ameliorate this selection bias .…”
Section: Nhs Health Checks and Low Moderate Risk Individualsmentioning
confidence: 99%
“…Because South Indian Asians have a greater risk of vascular events (2), it is imperative to validate a risk engine specifically aimed at this population living in India and in other countries where substantial migration has occurred (e.g. UK, USA).…”
mentioning
confidence: 99%